Pola Komunikasi Branch Collection Dalam Proses Penagihan Pembiayaan Bermasalah Kepada Debitur/Nasabah PT. Bank BTN KC Syariah Medan - Nurul Syahqilla, Mustapa Khamal Rokan (Education Achievement: Journal of Science and Research, 2022)
The high financing channeled to the public does not guarantee the smooth running of all debtor financing, and this is commonly referred to as a default, the number of debtors who fail to pay will affect the profits of Islamic banking, so to overcome this need a good communication pattern is in collecting problem financing from debtors. BTN KC Sharia Medan. The communication pattern is not only need a communication pattern only face to face, because in this era of globalization, digital communication patterns are very necessary and must be improved, such as making contracts and sanctions for customers who doesn’t report that their cellphone number has changed, or provide an unregistered phone number, and banks You must also be more careful in entering the debtor's number so that mistakes don't occur. Because so far there are many debtor numbers that cannot be contacted or misconnected, and face-to-face communication also needs to be improved, so far BTN KC Sharia Medan has used two communication patterns, namely digital communication patterns and digital communication patterns. face-to-face communication by visiting the debtor's house directly, the digital communication pattern is only about 20 percent resulting in clarity of customer payments, and if it continues to be unable to be contacted, a visit to the debtor's house will be made, but visits also sometimes create controversy between branch collections and debtors, because the debtor feel ashamed of the surrounding community, both family and neighbors and based on this, the purpose of this research is to find out the branch collection communication pattern in the process of collecting non-performing financing to debtors/customers either through digital or face-to-face. In this research, descriptive research method is used using a qualitative approach through interviews with respondents